МОДЕЛИРОВАНИЕ ЛИНГВИСТИЧЕСКОЙ НЕОПРЕДЕЛЕННОСТИ НА ОСНОВЕ Z-ЧИСЕЛ В СИСТЕМАХ МНОГОКРИТЕРИАЛЬНОГО ПРИНЯТИЯ РЕШЕНИЙ (World Science, 2020)
The article is devoted to the problem of multi criteria decision making under linguistic uncertainty. Information of different approaches for modelling linguistic uncertainty have been analyzed. The concept of z- numbers proposed by L. Zadeh have been presented. Z-number is presented as cortege of two fuzzy number A and B, where A is analyzed factor, B is reliability of an assessment. The method of conversion z- numbers into generalized fuzzy numbers have been applied. As test problem have been used supplier selection problem. As decision making model have been used group weighted average method. All calculations and results were presented.